Regulation of Cell Polarity by Exocyst-Mediated Trafficking - Polgar, Noemi (Cold Spring Harb Perspect Biol, 2018)
One requirement for establishing polarity within a cell is the asymmetric trafficking of intracellular vesicles to the plasma membrane. This tightly regulated process creates spatial and temporal differences in both plasma membrane composition and the membrane-associated proteome. Asymmetric membrane trafficking is also a critical mechanism to regulate cell differentiation, signaling, and physiology. Many eukaryotic cell types use the eight-protein exocyst complex to orchestrate polarized vesicle trafficking to certain membrane locales. Members of the exocyst were originally discovered in yeast while screening for proteins required for the delivery of secretory vesicles to the budding daughter cell. The same eight exocyst genes are conserved in mammals, in which the specifics of exocyst-mediated trafficking are highly cell-type-dependent. Some exocyst members bind to certain Rab GTPases on intracellular vesicles, whereas others localize to the plasma membrane at the site of exocytosis. Assembly of the exocyst holocomplex is responsible for tethering these vesicles to the plasma membrane before their soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE)-mediated exocytosis. In this review, we will focus on the role and regulation of the exocyst complex in targeted vesicular trafficking as related to the establishment and maintenance of cellular polarity. We will contrast exocyst function in apicobasal epithelial polarity versus front–back mesenchymal polarity, and the dynamic regulation of exocyst-mediated trafficking during cell phenotype transitions.